A multicentre snapshot study of the incidence of serious procedural complications secondary to central venous catheterisation. (16th December 2016) - Lathey, R. K.; Jackson, R. E.; Bodenham, A.; Harper, D.; Patle, V.; ,
Summary: Despite the high number of central venous access devices inserted annually, there are limited data on the incidence of the associated procedural complications, many of which carry substantial clinical risk. This point was highlighted in the recently published Association of Anaesthetists of Great Britain and Ireland 'Safe vascular access 2016' guidelines. This trainee‐led snapshot study aimed to identify the number of central venous catheter insertions and the incidence of serious complications across multiple hospital sites within a fixed two‐week period. Secondary aims were to identify the availability of resources and infrastructure to facilitate safe central venous catheter insertion and management of potential complications. Fifteen hospital sites participated, completing an initial resource survey and daily identification of all adult central venous catheter insertions, with subsequent review of any complications detected. A total of 487 central venous catheter insertions were identified, of which 15 (3.1%) were associated with a significant procedural complication. The most common complication was failure of insertion, which occurred in seven (1.4%) cases. Facilities to enable safer central venous catheter insertion and manage complications varied widely between hospitals, with little evidence of standardisation of guidelines or protocols.